First Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 22-27,1987. Day 6. Plenary session. Tape 1 of 3 - Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology, 1987)
Dr. Larry Moss, Superintendent of Green Bay Integrated School Board, describes the role of and skills needed by principal as mediator or arbitrator between various forces, e.g. parents and teachers. Also discusses some of these forces. Chair: Dr. Fred Buffett.